Extraction of Tannin From Ketapang Leaves (Terminalia catappa Linn) - Santi, Sintha Soraya; Irawati , Febriana; Prastica, Nita (Future Science)
Ketapang tree (Terminalia Catappa Linn) is a wild plant that trees is not including trees cultivated. Ketapang tree (Terminalia Catappa Linn) spread to almost all regions in Southeast Asia, including in Indonesia except Sumatra and Kalimantan are somewhat rare in nature. Study of Extraction Tannins from Ketapang leaves (Terminalia Catappa Linn) is done to find a solvent extraction and concentration on the extraction of tannins from leaves ketapang (Terminalia Catappa Linn) using ethanol solvent. The extraction process is done in a laboratory-scale batch and by the principles of solid-liquid extraction in a three-neck flask stirred for the specified time, namely 30, 60, 90, 120, 150 (minutes) with the concentration of solvent (ethanol) 60%, 70%, 80%, 85%, 90% as variable variables. While the weight of the sample remains variable 10 grams, ± 200 mesh particle size, extraction temperature 85 ? C, stirring speed 200 rpm, ethanol solvent type, settling time ± 30 minutes, the solvent volume 250 ml, distilled water adjuvant. The best condition of the tannin extraction using 85% ethanol for 120 minutes obtained 98.97% yield tannin concentration.